THE INFLUENCE OF ENVIRONMENTAL ACCOUNTING AND CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUE IN THE SECTOR MINING ON THE INDONESIAN STOCK EXCHANGE PERIOD 2020-2022 - Widya Lestari Nst; Nurhasanah; Husaini (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This research aims to determine the influence of environmental accounting and corporate social responsibility on company value. The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This research sample was taken using a purposive sampling technique with four criteria which resulted in 15 companies worth observing. This research uses multiple linear regression analysis using the SPSS program. In this research, the environmental accounting variable is measured using the PROPER ranking value, the corporate social responsibility variable uses the GRI 4 index and the company value variable is measured using the Tobin's q ratio. The research results show that environmental accounting has a significant negative effect on company value. And corporate social responsibility has a significant positive effect on company value.